AUTOMATING THE PROCESS OF APPLYING POLYMER COATING ON PARTS OF THE LIGHT INDUSTRY - HORIASHCHENKO, SERHIY; SYNUYK, OLEG; DRAPAK, GEORHIY; HORIASHCHENKO, KOSTYANTUN; ROMANETS, TARAS (Herald of Khmelnytskyi National University. Technical sciences, 2023)
In today's rapidly evolving manufacturing landscape, automation has become a driving force behind increased productivity, efficiency, and quality. One area where automation is making significant strides is the application of polymer coatings on parts of the light industry. By automating this process, manufacturers can achieve consistent and precise coating application, reduce labor costs, and improve overall production output. In this article, we explore the benefits and advancements of automating the polymer coating application process in the light industry.Automation in a small shop working with leather parts, several conditions and equipment considerations are essential was showed.Automation line with Automated Spray Systems significantly enhances efficiency and productivity in coating applications. These systems can operate continuously, 24/7, minimizing downtime and maximizing throughput. With faster application speeds and reduced cycle times, manufacturers can achieve higher production volumes within the same time frame. The automated process also eliminates the need for manual labor-intensive tasks, allowing workers to focus on more skilled and value-added activities. Overall, the integration of Robotic Arms and Automated Spray Systems leads to streamlined processes and improved manufacturing output.The automation of the process of applying polymer coatings on parts of the light industry offers numerous benefits ranging from increased precision and consistency to enhanced efficiency and productivity. By embracing automation, manufacturers can achieve superior coating quality, reduce labor costs, improve safety, and leverage Industry 4.0 technologies. As the manufacturing landscape continues to evolve, the adoption of automated systems in the light industry becomes increasingly crucial for staying competitive and meeting the demands of the modern market.
Keywords: Automation; application; polymer coatings; parts of light industry